Memories of My Town (Volume 8.0) (Finnish Literature Society / SKS, 2004)
Memories of My Town is an exploration into how town dwellers experience their environment in a complicated way. As people in urban milieus relate themselves to the environment, this takes place on many levels, where especially the time level becomes problematic. The urban buildings and settings can be looked upon as a kind of collective history, as carriers or witnesses of times past. But it is only the town dwellers that experience urban time itself, the time they live in, but through their memories also times past. In this past some elements take symbolically dense expressions. Through reliving and narrating their experiences the symbolically important factors in this urban relationship will be outlined for investigations concerning three towns, Helsinki, the capital, Vyborg, the ceded and lost Karelian town, and Jyväskylä, a town with dense commercial and cultural dimensions in the middle of Finland. The aim of the book is to use different theoretical concepts as guidelines in analysing the different narrative texts.